Congressional conservatism and the New Deal : the growth of the conservative coalition in Congress, 1933-1939 - Patterson, James T. (Kentucky paperbacks., 1967)
History faced by the disaster of depression, Congress in the early 1930s proved amenable to the far-reaching demands and programs presented to it by the newly elected President, Franklin D. Roosevelt, but by 1937 it showed increasing resistance, even outright opposition, to many New Deal measures. In this study, James T. Patterson examines this resurgence of conservative strength in Congress, focusing upon the personalities and backgrounds of the men involved and upon the key domestic issues which brought them together in an informal coalition opposed to executive plans, especially for the yea.